The Impact of the Quizlet App on Students' Mufradât Mastery: An Experimental Study - Ibnu Rawandhy N. Hula; Yousif Abdelmannan Mohamed Godat Arrashedy; Mohamad Lahay; Mukhtar I. Miolo; Damhuri Damhuri; Abdullah Sakka (AL-TA'RIB : Jurnal Ilmiah Program Studi Pendidikan Bahasa Arab IAIN Palangka Raya, 2024)
This research is motivated by the observation that 10th-grade students at MAS Al-Huda in Gorontalo City have low mastery of mufrad